Scalable speed-flow model for Singapore arterial roads - Lee, Chantal Christy Jia Yi (2018)
With the projected increase of total population from 6.5 to 6.9 million by 2030 in Singapore, there is a rising concern on the transport capacities of transport infrastructure. However, in recent years, with new bike-sharing companies starting up in Singapore, more people have chosen to cycle to travel instead of getting a motor vehicle which is far more expensive. Some people are taking the public transport. With more people taking the public transport or have chosen to cycle, which meant that there is a decrease in the population of motor vehicles, there is room to restructure the road infrastructure. The main focus of this study is to develop scalable speed-flow model for Singapore arterial roads and to find out if there is any effect on the capacity of the lane and speed of vehicles when lane width is decreased. With the decrease of lane width, the extra road space could be used as a lane for cyclists or to expand the pedestrian channel width. Traffic data were collected using video graphic approach from various sites during daytime dry weather conditions on weekdays – Tuesday, Wednesday and Thursday. Morning peak period (0700h to 1000h), afternoon off-peak period (1400h to 1600h) and evening peak period (1700h to 1930h) data were collected. The extracted data were modelled into different traffic speed-flow models. The Greenshields’ model was determined to have the best fit as contrasted to Generalised Drake’s, Drake-bell curve, Greenberg’s, Underwood’s, Polynomial and Quadratic model. Overall, the capacity of the lane (fast, middle and slow lane) increases as the lane width increases. The speed of the motor vehicles also increases as the lane width increases.